The Commander Aljarah bin Abdullah Al-Hakami Biography - Hamdoon Abdulla Al Sawaf, Khawla (Journal of College of Education, 2019)
This research was presented by a biography of a leading Muslim leader, Aljarah bin Abdullah Al-Hakami, who turned out to be a tribe of al-Hakam bin Saad , the clan of Mathehaj whose homes were in Tuhama, their capital Alkhsov, and after Islam, participated in the conquests and inhabited Kufa and Sham, and spread their influence to Egypt and revealed their relation with the Islam, where they islamized on 10 A.H/631 A.D and participated in the conquests of Levant and Egypt as the research showed the character of the Aljarah Ibn Abdullah Al-Hakami, who described it as the lieutenant colonel commander of the battalions and was a courageous hero. The thesis also showed the that his first appearance was in the fight Ibn Alasha'th under the reign of caliph Alwaleed bin Abdulmalik whose appointed him as governor  of Basra he has also held several administrative positions under the reign of caliph Suleiman bin Abdulmalik and under the reign of caliph Omar bin Abdul Aziz, who appointed him as governor  of Khorasan, and also on the reign of caliph Yazid ibn Abd al-Malik, who appointed him as governor  of Armenia and Azerbaijan as well as the reign of caliph Hisham ibn Abd as governor  Armenia and Azerbaijan when he was governor by the Umayyad Caliphs, he fought multiple battles with Al-Khaser and triumphed over them in many locations and continued to fight them until he was killed on 112 A.H/730 A.D in the Battle of Ardabil on the reign of Caliph Hisham ibn Abdul Malik.